1988
DOI: 10.1080/07391102.1988.10507715
|View full text |Cite
|
Sign up to set email alerts
|

Electron Microscopic and Physico-Chemical Studies of DNA Complexes with Synthetic Oligopeptides: Binding Specificity and DNA Compact Structures

Abstract: Binding to DNA of two synthetic peptides, Val-Thr-Thr-Val-Val-NH-NH-Dns and Thr-Val-Thr-Lys-Val-Gly-Thr-Lsy-Val-Gly-Thr-Val-Val-NH-NH-Dns (where Dns is a residue of 5-dimethylaminonaphthalene-1-sulfonic acid), has been studied by circular dichroism, electron microscopy and fluorescence methods. It has been found that these two peptides can self-associate in aqueous solution as follows from the fact that concentration-dependent changes are observed in the UV absorbance and fluorescence spectra. The two peptides… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

1991
1991
1999
1999

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 9 publications
1
4
0
Order By: Relevance
“…The compact rod-like structures are formed where peptide molecules occupy the majority of accessible positions on DNA The rod-like structures are about 8 nm thick in the preparations stained with uranyl acetate and are composed of two or three DNA duplexes lying side-by-side and interwoven (9). Similar structures were observed in the studies of DNA complexes with other peptides of similar nature (18,19).…”
Section: Dgtv: Dsdna Complexes At the Extremely Low And High Dsdna Cosupporting
confidence: 74%
See 1 more Smart Citation
“…The compact rod-like structures are formed where peptide molecules occupy the majority of accessible positions on DNA The rod-like structures are about 8 nm thick in the preparations stained with uranyl acetate and are composed of two or three DNA duplexes lying side-by-side and interwoven (9). Similar structures were observed in the studies of DNA complexes with other peptides of similar nature (18,19).…”
Section: Dgtv: Dsdna Complexes At the Extremely Low And High Dsdna Cosupporting
confidence: 74%
“…It has been interesting whether the further increase in trivaline concentration leads to the next step ofDNA compaction-wrapping ofthe rod-like particles-as it occurs in the case of the other peptides (19). In Figure 4 the electron micrographs are presented illustrating the preparations ofDG1V:DNAcomplexes at the DNA concentration 7.8*10-5 M of base pairs and that of peptide 0.7-2.1*10-4 M.…”
Section: Dgtv: Dsdna Complexes At the Extremely Low And High Dsdna Comentioning
confidence: 97%
“…Previous studies on binding of small ~ structure-forming peptides to DNA show that these peptides usually exist in a disordered conformation in aqueous solution, but assume a ~-like conformation upon binding DNA (20,39,41 ). A similar situation may take place when carboxyterminal residues oflambda cro interact with DNA.…”
Section: Spectra Of Complexes Between Cro Protein and Dna In The Fmentioning
confidence: 95%
“…In our previous work (26)(27)(28)(29)(30) we have shown that certain small peptides with inert amino acid side chains (such as trivaline) bind, in a ~-associated form, more tightly to poly(dG)•poly(dC) than to poly(dA)•poly(dT). Attachment of trivaline to the amino terminus of a netropsin analogue alters its binding specificity (30).…”
Section: Niko/aev Et A/mentioning
confidence: 98%